Traits Underlying Experimentally Evolved Dispersal Behavior in Tribolium castaneum - Michael D. Pointer; Lewis G. Spurgin; Ramakrishnan Vasudeva; Mark McMullan; Simon Butler; David S. Richardson (Journal of Insect Behavior, 2024)
Dispersal is an important behavior in many animals, with profound effects on individual fitness and the evolutionary trajectories of populations. This is especially true within taxa with particular life-history strategies, for example those that exploit ephemeral habitat. Further, dispersal is commonly seen to be part of behavioral syndromes - suites of traits that covary across behavioral contexts. The red flour beetle, Tribolium castaneum (Coleoptera, Tenebrionidae), is a major post-harvest crop pest responsible for large losses through the infestation of stored grain. In this system dispersal is known to have a strong genetic basis and differential artificial selection on dispersal traits produces strong phenotypic divergence. However, it is unknown which traits are able to rapidly evolve to produce these results, or which behavioral components underlie differences in dispersal. Using replicate lines of T. castaneum previously selected for divergent dispersal behavior, we test for correlated activity and movement patterns, morphology and substrate surface use. We find robustly repeatable associations between the dispersal phenotype and higher activity, straighter paths, larger body size (but not relative leg length) and increased tendency to remain at the surface of fodder. Together our results suggest that dispersal is part of a syndrome of traits in T. castaneum , and must be treated as such when considering the evolution of dispersal in this system, and in attempting to predict and control its spread.

Response of Female Frankliniella occidentalis (Pergande) to Visual Cues and Para-anisaldehyde in a Flight Chamber - Melanie M. Davidson; Ruth C. Butler; David A. J. Teulon (Journal of Insect Behavior, 2012)